Numerical simulation of plateau formation by an electron bunch on the distribution of an accelerating wakefield in a plasma - Maslov, V.I.; Ovsiannikov, R.T.; Delerue, N.; Kubytskyi, V.; Levchuk, I.P.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2020)
Over the past decade the production of multi-gigaelectrons from laser-driven and electron-bunch-driven plasma accelerators has been successfully demonstrated. However, applications require improvements of accelerated bunch size and its energy spread. One promising candidate to satisfy these requirements is to externally inject an electron bunch into an electron-bunch-driven plasma accelerator. We present studies on the optimization of the self-consistent distribution of an accelerating wakefield of plateau type, which can lead to improvement of final quality of the externally injected and accelerated electron bunch, using simulations with the particle-in-cell code LCODE. We quantified the effect of the injected bunch density on the plateau formation in the blowout regime.